2018
DOI: 10.3390/su10113958
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility Changes: Analysis of the Integrated Public Transport System of Bogotá

Abstract: Bogotá, a paradigmatic case of urban (re)development driven by transport interventions, began transforming its public transport system anew in mid-2010. It was not until 2012 when a gradual implementation of the new integrated public transport system of Bogotá (SITP in Spanish) began. By 2015, about 74% of the new bus routes were implemented. The considerable changes in supply and operational models for public transport during this period redefined travel conditions, having a direct impact on accessibility. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 36 publications
(49 reference statements)
1
26
0
Order By: Relevance
“…The effects of BRT systems on equity in cities in the global south have been documented in several past studies [12][13][14][39][40][41][42][43]. The findings in this literature suggest that while the systems often reduce travel times and costs and increase accessibility for low-income groups, the bulk of these benefits are often accrued among the middle class.…”
Section: Brt: Characteristics and Research On Their Social Benefitsmentioning
confidence: 95%
See 2 more Smart Citations
“…The effects of BRT systems on equity in cities in the global south have been documented in several past studies [12][13][14][39][40][41][42][43]. The findings in this literature suggest that while the systems often reduce travel times and costs and increase accessibility for low-income groups, the bulk of these benefits are often accrued among the middle class.…”
Section: Brt: Characteristics and Research On Their Social Benefitsmentioning
confidence: 95%
“…For example, the first phases of the Masivo Integrado de Occidente (MIO) BRT system of Santiago de Cali (Colombia) covered only 9% of city districts, located mostly in the central parts of the city, and skewing benefits in favor of the middle and upper-middle income groups [42,43]. In addition, fare policies frequently do not take into consideration affordability of the new systems for lower income groups, and the reorganization of existing transport services and restructuring of routes and fares associated with the implementation of BRT systems can limit the distribution of travel efficiency benefits to lower income households, particularly that these households tend to live in outlying areas with poor quality or no feeder services [15,39,42]. These studies have found that the enhancement of pro-poor benefits requires targeted policies such as integration with other transit, targeted fare subsidies, and the provision of affordable housing near stations.…”
Section: Brt: Characteristics and Research On Their Social Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that it is significant to allocate appropriate slack time to provide effective flexible line service. Dijosephl et al [37][38][39] developed an optimization algorithm to search for the maximal-profits optimal solution by considering the public transport network and passenger demand, as well as optimized the regional public transport system and financially sustainable operation.…”
Section: Coordination and Optimization Of Rail And Public Transportmentioning
confidence: 99%
“…Two ways were proposed including public control and restriction, as well as public investment in low-emission transport infrastructure. Some literature also focused on the transport behavior, which concluded that major transport policy that could reduce passenger travel levels would be most effective in transport emission cuts [22,[39][40][41].…”
Section: Literature Reviewmentioning
confidence: 99%